Cardioembolic but Not Other Stroke Subtypes Predict Mortality Independent of Stroke Severity at Presentation - Latha Ganti Stead; Rachel M. Gilmore; M. Fernanda Bellolio; Anunaya Jain; Alejandro A. Rabinstein; Wyatt W. Decker; Dipti Agarwal; Robert D. Brown (Stroke Research and Treatment)
Introduction. Etiology of acute ischemic stroke (AIS) is known to significantly influence management, prognosis, and risk of recurrence. Objective. To determine if ischemic stroke subtype based on TOAST criteria influences mortality. Methods. We conducted an observational study of a consecutive cohort of patients presenting with AIS to a single tertiary academic center. Results. The study population consisted of 500 patients who resided in the local county or the surrounding nine-county area. No patients were lost to followup. Two hundred and sixty one (52.2%) were male, and the mean age at presentation was 73.7 years (standard deviation, SD = 14.3). Subtypes were as follows: large artery atherosclerosis 97 (19.4%), cardioembolic 144 (28.8%), small vessel disease 75 (15%), other causes 19 (3.8%), and unknown 165 (33%). One hundred and sixty patients died: 69 within the first 30 days, 27 within 31–90 days, 29 within 91–365 days, and 35 after 1 year. Low 90-, 180-, and 360-day survival was seen in cardioembolic strokes (67.1%, 65.5%, and 58.2%, resp.), followed for cryptogenic strokes (78.0%, 75.3%, and 71.1%). Interestingly, when looking into the cryptogenic category, those with insufficient information to assign a stroke subtype had the lowest survival estimate (57.7% at 90 days, 56.1% at 180 days, and 51.2% at 1 year). Conclusion. Cardioembolic ischemic stroke subtype determined by TOAST criteria predicts long-term mortality, even after adjusting for age and stroke severity.